PENERAPAN APLIKASI DOKUMENTASI EKSPOR IMPOR DI LABORATORIUM SIMULASI EKSPOR IMPOR DALAM MENGHADAPI AEC - Mulyadi Mulyadi; Arif Rahman Hakim (Lembaga Pengabdian pada Masyarakat, 2022)
Abstract This activity aimed to provide skills of students on export import documentation in order to compete in the ASEAN Economic Community (AEC) era. It is planned in the form of training of export-import and designing application for export-import document. The application will be implemented in the laboratory as the learning facility for international trade. Students are the main target of this activity must be given the technical understanding of the document import-export through training first. The next stage is to provide training related to the document through a simulation in the laboratory. The laboratory used is Export-Import Laboratory in FEB UNS which has been licensed by Indonesia Export Training Center (IETC) of the Ministry of Commerce. First output is the students have competence in controlling and planning applications import export documentation certified by BNSP through LSP-EII. Second output is applications which can be used to simulate export documents in a laboratory simulation of the export import in FEB UNS. Keyword: export-import, documentation, simulation